Living Qur'an: The Meaning of Gratitude in The Tradition Sudah Tuai (Case Study In Koto Salak Kerinci Village) - Muhammad Fadhlan; Annisa Ulfitri; Florian Pohl (International Journal of Islamic Education, Research and Multiculturalism (IJIERM), 2023)
Abstract: Indonesia highly upholds cultural values, especially Islamic cultural values. This research explains how the Koto Salak people's interpretation of the Qur'anic verse about gratitude, namely QS. Ibrahim verse 7 as a form of gratitude from the people of Koto Salak Village to Allah SWT for the abundance of rice harvests and the practice of community gratitude is manifested in the form of the Kenduri Sudah Tuai tradition. This research is a Qualitative research with an Ethnographic approach. The ethnographic approach used in this study to examine cultural culture in the Koto salak community towards the meaning of Gratitude after the holding of kenduri has reaped Data collected in this study there are three ways, namely: Observation, Interview, and Documentation. After the data was obtained, the researchers conducted data analysis with the approach of Miles and Huberman and Saldana, namely in Four ways; 1) Collecting data, 2) Blending Data, 3) Condensing Data, 4) and Infering with Data. The results of the study are as follows: 1) Kenduri has been reaped as a form of Gratitude to God, 2) As a container to strengthen friendship, 3) As a container for almsgiving, 4) Glorifying guests, 5) As a form of rejecting bala. Keywords: Gratitude, Kenduri Has Reaped, Living Qur'an